Sjælesorgstypologi i anvendelse: Et indblik i dansk sjælesorg over for kirkenysgerrige (Tidsskrift for Praktisk Teologi, 2022)
In 2021, a podcast called Sjælesorg (Pastoral Care) was published at the official home- page of the Evangelical-Lutheran Church in Denmark (folkekirken.dk). This podcast consists of ten pastoral care conversations that allow a view into how Danish pastors practice pastoral care with people for whom church and Christianity have so far been present in the cultural background. In the article, I use the podcast as a case for discussing Norwegian theologian Tor Johan Grevbo’s eight-fold typology of pastoral care. I argue that this typology can be used to analyze concrete conversations of pastoral care. I also discuss the limits of using the typology in this way. On this basis, I suggest a more flexible graphic presentation of the typology, from spectrum to circle. I use this graphic presentation to summarize my conclusions about contemporary Danish pastoral care of people who are curious about church and Christianity.